PERLINDUNGAN HUKUM TERHADAP KONSUMEN DAN PELAKU USAHA DALAM TRANSAKSI JUAL BELI ONLINE MELALUI METODE PEMBAYARAN CASH ON DELIVERY (COD) - Nurlani, Meirina (Faculty of Law, University of Palembang, 2024)
Legal protection for consumers and business actors in online buying and selling deals using the Cash On Delivery (COD) payment system is an personification of fighting for the rights that consumers and business actors have. The significance of furnishing legal protection aims to overcome problems that frequently do. Problems that do to consumers include the condition of the goods not being as promised, detainments in delivery, as well as fraud issues. Meanwhile, problems that frequently do with business actors are damage to goods during delivery or returning goods that don't reach the dealer. The significance of applicable legal protection for consumers and business actors is not only aimed at fostering sense of trust, convenience, comfort and security for all parties involved in online buying and selling deals using the COD system. still, the end of this legal protection is also to give applicable legal arrangements for all parties involved to give legal certainty for online buying and selling deals using the COD payment system.